Prevalence of unfavorable outcome in acute poisoning and associated factors at the University of Gondar comprehensive specialized hospital, Gondar, Northwest Ethiopia: a hospital-based cross-sectional study - Waktola, Leta Gemeda; Melese, Endalkachew Belayneh; Mesfin, Nebiyu; Altaye, Kassaye Demeke; Legese, Gebrehiwot Lema (Frontiers in Public Health, 2023)
Background: Acute poisoning is a medical emergency in which the toxic effects occur almost immediately, usually within hours from the time of exposure, and can result from exposure to excessive doses of any chemical. Acute poisoning is a medical emergency. It is the common cause of emergency admission, which may result in morbidity and mortality. There are a lot of factors that are associated with an increased magnitude of mortality and complication. Therefore this study was carried out to assess the clinical characteristics of patients, unfavorable outcomes of acute poisoning, and associated factors to improve the quality of care, resource utilization, and decrease mortality. Objective: This study aimed to assess the outcome and associated factors among acute poisoning patients at the University of Gondar Comprehensive Specialized Hospital, Gondar, North West, Ethiopia 2021. Methods: Prospective follow-up study was conducted from January 2021 to September 2021 at the University of Gondar Comprehensive Specialized Hospital, Gondar, North West, Ethiopia. Data was collected using a comprehensively organized and pretested interviewer-administered questionnaire. The data was entered using EPI data version 4.6.0 statistical software and then exported to Stata 14 for analysis. The data was analyzed for its descriptive statistics. Statistical analysis to identify factors associated with the unfavorable outcome of acute poisoning was performed using bivariate and multivariate logistic regression models. The result is presented in the form of tables, figures, and text using frequencies and summary statistics such as mean, SD, median, IQR, and percentage. Result: A total of 233 patients were in the study. The prevalence rate of unfavorable poisoning outcomes was 17.6% (95% CI: 13.2, 23.1). The result of multivariate logistic regression analysis showed that the independent factors associated with unfavorable outcomes were having known chronic medical comorbidities (AOR: 3.846(1.619, 9.574); P value: 0.014)) and hospital stay <48hrs (AOR: 6.57(2.03, 21.273); P value: 0.002)). Conclusion: The rate of unfavorable poisoning outcomes was high in patients with acute poisoning. Having known medical comorbid illness and hospital stay <48hrs were found to be associated with unfavorable outcome